2018
DOI: 10.1177/1559325818755238
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Low-Dose-Rate Ionizing Radiation Stimulates Adaptive Functional and Molecular Response in Human Aortic Endothelial Cells in a Threshold-, Dose-, and Dose Rate–Dependent Manner

Abstract: A central question in radiation protection research is whether low-dose and low-dose-rate (LDR) exposures to ionizing radiation play a role in progression of cardiovascular disease. The response of endothelial cells to different LDR exposures may help estimate risk of cardiovascular disease by providing the biological mechanism involved. We investigated the effect of chronic LDR radiation on functional and molecular responses of human aorta endothelial cells (HAoECs). Human aorta endothelial cells were continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 67 publications
2
14
0
Order By: Relevance
“…Nonetheless, decreased inflammatory cytokine production, reduced migration, and increased chemotaxis in macrophages ha ve also been observed [156]. A recent study by our group showed the importance of dose rate on endothelial cells ' molecular and functional responses; upregulation of antioxidant and anti -inflammatory gene expression after chronic low dose rate exposure (6 mGy/h) produced an adaptive response even when the dose reached 2 Gy [157].…”
Section: Immune/inflammatory Reactionsmentioning
confidence: 76%
“…Nonetheless, decreased inflammatory cytokine production, reduced migration, and increased chemotaxis in macrophages ha ve also been observed [156]. A recent study by our group showed the importance of dose rate on endothelial cells ' molecular and functional responses; upregulation of antioxidant and anti -inflammatory gene expression after chronic low dose rate exposure (6 mGy/h) produced an adaptive response even when the dose reached 2 Gy [157].…”
Section: Immune/inflammatory Reactionsmentioning
confidence: 76%
“…Since no DNA DSBs are observed, the changes in 8-oxo-dG and FRAP levels can also be explained by an adaptive response 4,[93][94][95] . Since 8-oxo-dG excretion and antioxidant capacity both increase in children, it could indicate that the intracellular defence mechanisms are being 'primed' , i.e.…”
Section: Discussionmentioning
confidence: 99%
“…As a second step, and despite the limitations described above, a small subset of 24 reports involving original human data mentioned in the title or in the abstract was identified. It represents 8.8% and 5.1% of all the inventoried papers, respectively 15 -38 (Tables 1 and 2). By analyzing these reports, 3 major conclusions can be drawn: – There are few original human data about hormesis.…”
Section: Radiation Hormesis In Humans: Few Data Available In Literaturementioning
confidence: 99%